Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am finding (and computing the limits) of all vertical and horizontal asymptotes of ${5(e^x) \over (e^x)-2}$. I have found the vertical asymptote at $x=ln2$. I have also found the horizontal asymptote at y=5 by calculating the limit of the function at positive infinity. I know that to find the other horizontal asymptote (which is at $y=0$, based on the graph), I need to calculate the limit at negative infinity, but I cannot get it to equal zero.

my calculations thus far: lim as x approaches negative infinity of the function is equal to the limit as x approaches infinity of ${5 \over (e^x)-2}$, which I found by dividing both numerator and denominator by $e^x$.

but I just keep getting that the limit at negative infinity is the same as the limit at positive infinity - ${5\over(1-0)}$ or 5 - which I know is not correct.

what am i missing?

share|improve this question
add comment

2 Answers 2

Let $y=-x$; then you can more easily see that

$$\lim_{x\to-\infty}e^x=\lim_{y\to+\infty}e^{-y}=\lim_{y\to+\infty}\frac1{e^y}=0\;,$$

since the denominator $e^y$ is blowing up rather explosively as $y\to\infty$.

Going back to the original problem,

$$\lim_{x\to-\infty}\frac{5e^x}{e^x-2}=\frac{\lim\limits_{x\to-\infty}5e^x}{\lim\limits_{x\to-\infty}e^x-2}=\frac0{0-2}=0\;.$$

share|improve this answer
    
okay, I understand the concept - that the limit of 5e^x or e^x is 0 as either approaches negative infinity - but why could I not get that with the algebra I did (namely dividing numerator and denominator by e^x, which is how I thought you solved infinity limits)? –  theialux Sep 30 '12 at 1:54
    
@theialux: It isn’t always necessary, and this is a case in which it isn’t. You can do it that way, but then you have to evaluate correctly the resulting limit: in $\lim\limits_{x\to-\infty}\frac5{1-\frac2{e^x}}$ the denominator $\to-\infty$, so the whole thing $\to 0$. –  Brian M. Scott Sep 30 '12 at 2:11
    
alright, thanks. –  theialux Sep 30 '12 at 2:19
add comment

Let us begin with the calculation: $${5(e^x) \over e^x-2}={5(e^x-2)+`10 \over e^x-2}=5+{`10 \over e^x-2}$$ Therefore, as $$x\rightarrow -\infty$$, $$e^x\rightarrow 0$$, and $$5+{`10 \over e^x-2}\rightarrow 5+ {10\over0-2}=5-5=0.$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.